Factors contributing to job satisfaction among school counselors - Ooi, Pei Boon; Wan Jaafar, Wan Marzuki; Baba, Maznah (Elsevier, 2015)
Emerging from the Social Cognitive Theory by Bandura, this study of 541 Malaysia school counselors examined the effect of sources of counseling self-efficacy on counselors’ job satisfaction in counseling settings. Based on the Structural Equation Model, the study explored the strength of efficacy information and its effect on counseling self-efficacy and job satisfaction. Sources of Counseling Self-Efficacy Scale was adopted and modified and significant result was found between sources of counseling self-efficacy and job satisfaction. Counseling self-efficacy significantly mediated the sources of counseling self-efficacy and job satisfaction. Future recommendations, suggestions to strengthen self-efficacy and limitations were discussed.